2013
DOI: 10.1002/pca.2483
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Discrimination of Different Tomato Cultivars Based on Their Volatile Fingerprint in Relation to Lycopene and Total Phenolics Content

Abstract: The tomato cultivars studied were easily discriminated based on their characteristic volatile profile that was obtained using the reliable ITEX/GC-MS technique. Principal component analysis revealed, in addition to volatile compounds, the important role played by the total phenolic content in tomato cultivar discrimination, which is highly correlated with phenotypic and biochemical differences between tomato cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 26 publications
2
35
0
2
Order By: Relevance
“…The extraction of volatile compounds was made according to the method described by Socaci et al, (2014) [32]. In brief, five grams of each sourdough sample was placed in a 20 mL headspace vial, incubated for 20 min at 60 • C, under continuous agitation.…”
Section: Extraction and Analysis Of Volatile Compounds By Itex/gs-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of volatile compounds was made according to the method described by Socaci et al, (2014) [32]. In brief, five grams of each sourdough sample was placed in a 20 mL headspace vial, incubated for 20 min at 60 • C, under continuous agitation.…”
Section: Extraction and Analysis Of Volatile Compounds By Itex/gs-msmentioning
confidence: 99%
“…The analysis of volatile compounds was carried out on a gas chromatograph-mass spectrometer GC-MS model QP-2010 (Shimadzu Scientific Instruments, Kyoto, Japan), using the method described by Socaci et al, (2014) [32]. The separation of volatile compounds was performed on a Zebron ZB-5 ms capillary column of 30 m × 0.25 mm i.d and 0.25 mm film thickness.…”
Section: Extraction and Analysis Of Volatile Compounds By Itex/gs-msmentioning
confidence: 99%
“…It was found that melatonin is present in a lot of different types of foods and food supplements. The quantity of melatonin in the most common foods is variable: banana -0.47 ng/g [7], apple -0.05 ng/g [8], kiwifruit 0.02 ng/g [8], pineapple -0.04 ng/g [8], strawberry -0.01 ng/g [8], montmorency tart cherry -13.46 ng/g [9], orange -0.15 ng/g [10], mango -0.70 ng/g [10], papaya -0.24 ng/g [10], tomato -8-16 pg/g [11,12], red wine -17.07 ng/g [13,14], beer -1.43 ng/g [13], bread crumb 3 -1.57 ng/g [15], walnuts -1.0 ng/g [15,16] , olive oil -53-119 pg/mL [17], almonds -39 ng/g [18], coffea canephora -115.25 ± 6µg/ g [19], beef -2.1 ng/g [20], salmon -3.7 ng/g [20].…”
mentioning
confidence: 99%
“…The aqueous extracts (Achillea melifolium infusion and pepino juice) were screened for total phenolics content using the Folin-Ciocalteu reagent, according to Socaci et al (2013) and antioxidant activity (2,2-diphenyl-1-picrylhydrazyl method) (Anesini et al,2008) …”
Section: Methodsmentioning
confidence: 99%